2017
DOI: 10.1200/jgo.2016.004960
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Impact of Multidisciplinary Tumor Boards on Patient Management: A Prospective Study

Abstract: PurposeMultidisciplinary tumor boards (MTBs) have become commonplace. The use, attendance, and function of MTBs need continued assessment and improvement.MethodsWe prospectively recorded and assessed all cases presented at MTBs between October 2013 and December 2014. Data were collected before and during each MTB. Data were analyzed using SPSS for Windows version 23 (SPSS, Chicago, IL).ResultsFive hundred three cases were presented: 234 cases (46%) at GI cancer MTBs, 149 cases (29.6%) at breast cancer MTBs, 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 22 publications
2
57
0
2
Order By: Relevance
“…They examine each patient's clinical, pathologic, and molecular information, review the literature and available resources, carry out discussions to reach a consensus if possible, and make treatment suggestions [89]. Previous studies have shown that interdisciplinary tumor boards can result in significant changes in treatment decisions [90][91][92][93]. The impact of MTB on outcomes has not yet been studied indepth, but they can help to identify patients for clinical trials, educate participants, facilitate collaboration, and ensure that providers across multiple locations are testing and treating patients in a uniform and consistent manner, based on clinical practice guidelines and best available evidence.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…They examine each patient's clinical, pathologic, and molecular information, review the literature and available resources, carry out discussions to reach a consensus if possible, and make treatment suggestions [89]. Previous studies have shown that interdisciplinary tumor boards can result in significant changes in treatment decisions [90][91][92][93]. The impact of MTB on outcomes has not yet been studied indepth, but they can help to identify patients for clinical trials, educate participants, facilitate collaboration, and ensure that providers across multiple locations are testing and treating patients in a uniform and consistent manner, based on clinical practice guidelines and best available evidence.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…Another more recent study by Charara et al 10 in 2017 focused more on the decision-making process involved in an MTB. However, of 503 cases presented, only 12 resulted in a change in radiology findings, and only 6 cases had a change in pathology.…”
mentioning
confidence: 99%
“…Although this study did not focus on second opinions, it was noted in the paper that half of the patients in each of the radiology and pathology change groups had second opinions. 10 …”
mentioning
confidence: 99%
“…Part of this inter-centre variability could be due to legitimate inter-centre differences in the organizational models of the MTBs. Although a few studies have questioned whether it is really necessary to present all patients to a MTB [15], we believe-as recent studies have shown [16]-that this is important because it may alter the diagnosis or treatment plan in a substantial proportion (20-50%) of cases. The main concerns about the value of the MTP appear to be the structure and composition of the board itself and the thoroughness of decision-making and follow up.…”
Section: Presentation Of Cases To the Mtb And Departmental Clinical Smentioning
confidence: 97%